Integrative omics analysis reveals distinct adaptations of bongkrekic acid producing Burkholderia gladioli pathovar cocovenenans strains - He, Jiale; Zhao, Lingguo; Sun, Yunke; Chen, Qingliang; Chen, Jun; Zhang, Yingdan; Yang, Liang; Liu, Yang; Lei, Lei (Frontiers in Microbiology, 2026)
IntroductionBurkholderia gladioli pathovar cocovenenans is an emerging pathogen, with its key toxin, bongkrekic acid (BA), encoded by the bon gene cluster. BA has been linked to several fatal food poisonings. Although its toxicity is well-known, its ecological and evolutionary role in bacterial adaptation and pathogenicity remains unclear. This study aims to clarify the phylogenetic differentiation, genomic features, and ecological strategies of BA-producing strains, and develop rapid detection methods to reduce food safety risks.MethodsWe performed a comprehensive genomic analysis of 305 Burkholderia strains, including 34 isolated strains and 271 publicly available genomes. Phylogenetic reconstruction traced the evolutionary trajectory, and comparative genomics identified genetic differences between BA-producing and non-producing strains. Transcriptomic and metabolomic profiles were generated under controlled conditions to compare gene expression and metabolic features. Specific probes were also designed for rapid detection of BA and toxoflavin.ResultsPhylogenetic analysis revealed a clear differentiation between strains with and without the bon gene cluster, indicating that BA synthesis plays a crucial role in the evolution of Burkholderia. The acquisition of the bon gene cluster is hypothesized to have occurred at a later stage in evolution. Although the distribution of virulence factors was generally similar between the two groups, the bon gene cluster was associated with specific virulence traits, such as pyruvate metabolism and secretion systems. All strains harboured β-lactam antibiotic resistance genes within their genomes. Transcriptome and metabolome analyses revealed elevated expression of type III secretion system (T3SS)-associated genes in BA-producing strains, alongside increased organic acid and lipid metabolism. The newly developed probes enable specific, rapid detection of BA and toxoflavin, providing an effective tool for strain screening.ConclusionGenomic, transcriptomic, and metabolomic analyses show that the bon gene cluster is highly conserved in Burkholderia gladioli and predominantly clustered within specific branches of the phylogenetic tree. The presence of this gene cluster correlates with specific pathogenic traits and is associated with alterations in T3SS expression and metabolic characteristics, which are closely linked to bacterial adaptability across diverse ecological environments. The developed toxin-specific probes provide a reliable tool for rapid detection, supporting future monitoring and control efforts.